Gingiva Equivalents Secrete Negligible Amounts of Key Chemokines Involved in Langerhans Cell Migration Compared to Skin Equivalents - Ilona J. Kosten; Jeroen K. Buskermolen; Sander W. Spiekstra; Tanja D. de Gruijl; Susan Gibbs (Journal of Immunology Research)
Both oral mucosa and skin have the capacity to maintain immune homeostasis or regulate immune responses upon environmental assault. Whereas much is known about key innate immune events in skin, little is known about oral mucosa. Comparative studies are limited due to the scarce supply of oral mucosa for ex vivo studies. Therefore, we used organotypic tissue equivalents (reconstructed epithelium on fibroblast-populated collagen hydrogel) to study cross talk between cells. Oral mucosa and skin equivalents were compared regarding secretion of cytokines and chemokines involved in LC migration and general inflammation. Basal secretion, representative of homeostasis, and also secretion after stimulation with TNFα, an allergen (cinnamaldehyde), or an irritant (SDS) were assessed. We found that proinflammatory IL-18 and chemokines CCL2, CCL20, and CXCL12, all involved in LC migration, were predominantly secreted by skin as compared to gingiva. Furthermore, CCL27 was predominantly secreted by skin whereas CCL28 was predominantly secreted by gingiva. In contrast, general inflammatory cytokines IL-6 and CXCL8 were secreted similarly by skin and gingiva. These results indicate that the cytokines and chemokines triggering innate immunity and LC migration are different in skin and gingiva. This differential regulation should be figured into novel therapy or vaccination strategies in the context of skin versus mucosa.